F Formulasi Sediaan Gel Ekstrak Lidah Buaya (Aloe Barbadensis) Dan Daun Sambung Nyawa (Gynura procumbens) Sebagai Alternatif Penyembuhan Luka - Dinofitri, Hanifah; Cathelya, Bunga; Idamanda, Rahma; Putri Aulia, Bilqis; Rizamevia, Fhidila; Maharini, Indri; Sani K, Fathnur (LPPM Universitas Sari Mulia, 2025)
Background: Wound care can involve both chemical and natural substances to accelerate the healing process. Aloe vera is known for its wound-healing properties due to the presence of saponins. Similarly, sambung nyawa leaves aid in wound healing because they contain flavonoids. Combining extracts from aloe vera and sambung nyawa is expected to enhance the healing process. Gel formulations are advantageous as they allow for prolonged drug contact with the wound and protect it from external contamination.Objective: This study aims to evaluate the effect of varying concentrations of Carbopol 940 as a gelling agent on the physical properties and stability of the gel, as well as to assess the effectiveness of the gel in promoting the healing of excision wounds.Methodology: The method used in this study is experimental. The gel formulations consist of four formulas with varying concentrations of sambung nyawa leaf extract and Carbopol. Evaluation of the gel's physical properties includes organoleptic tests, homogeneity, spreadability, adhesiveness, pH, viscosity, and stability tests. The excision wound healing test was conducted on mice using six treatment groups. The observed parameter was the percentage of wound healing. Data analysis was performed descriptively and statistically using One-Way ANOVA.Results: The evaluation results of the formulation showed that the developed formula met the standards for physical properties and stability. The best wound-healing effectiveness was observed in treatment group 4, which contained 4% ethanol extract of aloe vera, 5% sambung nyawa leaves, and 2% Carbopol 940.Conclusion: The variation in Carbopol 940 concentration affects the physical properties and stability of the gel formulation. The effectiveness of excision wound healing indicates that higher concentrations of sambung nyawa leaf extract result in better wound-healing efficacy.